2000
DOI: 10.1007/s004180000158
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the distribution of synemin, paranemin, and plectin in skeletal muscles of wild-type and desmin knock-out mice

Abstract: Mice lacking the gene encoding for the intermediate filament protein desmin have a surprisingly normal myofibrillar organization in skeletal muscle fibers, although myopathy develops in highly used muscles. In the present study we examined how synemin, paranemin, and plectin, three key cytoskeletal proteins related to desmin, are organized in normal and desmin knock-out (K/O) mice. We show that in wild-type mice, synemin, paranemin, and plectin were colocalized with desmin in Z-disc-associated striations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 41 publications
1
28
0
2
Order By: Relevance
“…In mature muscles of mice, we have found that synemin and paranemin, together with plectin, are colocalized with desmin in Z-disc-associated striations and at the sarcolemma, where they display topological and structural relationships. Furthermore, the localization of synemin in longitudinal sections of skeletal muscles from desmin knockout mice was markedly affected by the absence of desmin, whereas that of plectin was the same as in normal mice [28]. We do not yet know whether synemin compensates for or accentuates the absence of functional desmin in certain muscle types and if so whether this reflects its differing impacts on striated and smooth muscles [29].…”
Section: Analyses Bymentioning
confidence: 91%
“…In mature muscles of mice, we have found that synemin and paranemin, together with plectin, are colocalized with desmin in Z-disc-associated striations and at the sarcolemma, where they display topological and structural relationships. Furthermore, the localization of synemin in longitudinal sections of skeletal muscles from desmin knockout mice was markedly affected by the absence of desmin, whereas that of plectin was the same as in normal mice [28]. We do not yet know whether synemin compensates for or accentuates the absence of functional desmin in certain muscle types and if so whether this reflects its differing impacts on striated and smooth muscles [29].…”
Section: Analyses Bymentioning
confidence: 91%
“…Synemin does not polymerize by itself but incorporates into vimentin and desmin IFs and, unlike vimentin and desmin, binds to vinculin (10 -13). In addition, synemin incorporation into costameres and myotendinous junctions does not require a desmin IF network (9). These properties suggest that in myocytes, synemin docks IFs into vinculin-containing junctions.…”
mentioning
confidence: 89%
“…Vinculin is a major component of several junctions with which vimentin or desmin IFs interact, such as costameres and myotendinous connections (8). Another IF protein, synemin, also associates with these junctions (9,10). Synemin does not polymerize by itself but incorporates into vimentin and desmin IFs and, unlike vimentin and desmin, binds to vinculin (10 -13).…”
mentioning
confidence: 99%
“…Early in mammalian skeletal [Sejersen and Lendahl, 1993] and cardiac [Kachinsky et al, 1995] muscle differentiation, desmin is co-expressed with vimentin (MIM 193060) and the large IF protein nestin (MIM 600915). Later, as the muscle matures, desmin is co-expressed with the large IF proteins synemin and paranemin [see Carlsson et al, 2000]. Like other IF proteins, denatured desmin assembles into filaments following the removal of denaturants.…”
Section: Introductionmentioning
confidence: 99%